Preparation method of modified zinc negative electrode, modified zinc negative electrode and aqueous zinc ion battery
By forming a passivation-activation structure on the surface of the zinc anode and treating the zinc anode with tetrahydroxymethyl phosphorus chloride solution, the problems of complex preparation and high cost of zinc anode modification technology are solved. This achieves zinc dendrite suppression and reduction of side reactions, thereby improving the cycle performance and stability of aqueous zinc-ion batteries.
Patent Information
- Application Number
- CN202511696597.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2025-12-16
- Estimated Expiration
- 2045-11-19
AI Technical Summary
Existing zinc anode modification technologies are complex to prepare, costly, and difficult to effectively suppress dendrites and side reactions, which affect the cycle performance and commercial application of aqueous zinc-ion batteries.
The zinc anode surface was treated with tetrahydroxymethyl phosphorus chloride solution to form a passivation-activation structure. By forming a thin protective layer on the zinc anode surface, the formation of zinc dendrites was inhibited and side reactions were reduced.
It effectively suppresses zinc dendrites, improves the cycle life of aqueous zinc-ion batteries, reduces manufacturing difficulty and cost, and maintains the battery's kinetic performance.
Smart Images

Figure CN121149249A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc-ion battery technology, and in particular to a method for preparing a modified zinc anode, the modified zinc anode, and an aqueous zinc-ion battery. Background Technology
[0002] Zinc, as an anode material, possesses advantages such as high theoretical capacity, low redox potential, and abundant reserves. Furthermore, zinc exhibits high chemical stability in aqueous solutions. Therefore, aqueous zinc-ion batteries based on zinc anodes show great promise in grid-scale energy storage. However, zinc anodes still face several challenges in practical applications, including zinc dendrites formed by uneven zinc deposition, and side reactions such as corrosion, passivation, and hydrogen evolution caused by water in the electrolyte.
[0003] Currently, modification strategies for addressing the above problems mainly include electrolyte optimization, separator optimization, and negative electrode protection / structural design. Methods for negative electrode protection / structural design include: ① Negative electrode protective layer construction. This involves introducing a protective layer onto the zinc negative electrode using physical or chemical methods, or generating a solid electrolyte interface in situ. ② Negative electrode structural design. This involves designing a 3D porous current collector, or using porous materials as the zinc carrier.
[0004] However, these methods still have some shortcomings. For example, the preparation of the interface protective layer requires complex techniques such as vacuum deposition and atomic layer deposition, which are costly and difficult to scale up. The interfacial bonding between the artificial protective layer and the zinc anode is weak, and it is prone to detachment and failure during long-term cycling. An overly dense protective layer can severely hinder Zn absorption. 2+ This increases polarization and reduces the rate performance of the battery. The development and design of 3D current collectors are complex and difficult to industrialize.
[0005] Therefore, developing a zinc anode modification technology that is simple to implement, low in cost, can effectively suppress dendrites and side reactions, and does not impair battery kinetic performance is crucial for promoting the commercial application of aqueous zinc-ion batteries. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a modified zinc anode, a modified zinc anode, and an aqueous zinc-ion battery, thereby solving the problems of difficult and costly preparation of modified zinc anodes.
[0007] To achieve the above objectives, the present invention provides a method for preparing a modified zinc anode, comprising the following steps: S1. Dilute the 80% tetrahydroxymethyl phosphorus chloride solution to a certain concentration, stir evenly, and form a treatment solution; S2. After cutting the zinc negative electrode, perform surface treatment on the zinc negative electrode; S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur; S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0008] Preferably, in step S1, the volume concentration of tetrahydroxymethylphosphoric acid in the prepared treatment solution is 1%-7%.
[0009] Preferably, in S2, the thickness of the zinc negative electrode is 100 μm, and the zinc negative electrode is pure zinc foil or pure zinc plate.
[0010] Preferably, in step S2, the surface treatment of the zinc anode specifically involves: sequentially ultrasonically cleaning the zinc anode with deionized water and ethanol for 30 minutes and with an ultrasonic power of 25W.
[0011] Preferably, in step S3, the reaction time is 0.5h-10h.
[0012] Preferably, in step S4, the drying temperature of the vacuum drying oven is 60°C and the drying time is 4 hours.
[0013] A modified zinc anode, comprising: Zinc anode body, A passivation-activation structure is formed in situ on the surface of the zinc anode body, and the passivation-activation structure is formed by the above preparation method.
[0014] Preferably, the thickness of the zinc anode body is 100 μm, and the zinc anode body is pure zinc foil or pure zinc plate.
[0015] An aqueous zinc-ion symmetric battery includes a zinc electrode, a separator, an electrolyte, and a zinc electrode, wherein the zinc electrode is the modified zinc negative electrode described above.
[0016] An aqueous zinc-ion battery full cell includes a zinc negative electrode, a separator, an electrolyte, and a positive electrode, wherein the positive electrode is an ammonium vanadate positive electrode.
[0017] Preferably, the electrolyte for the symmetrical battery and the full battery is a 2 mol / L ZnSO4 solution, and the separator is a glass fiber separator or commercial filter paper.
[0018] The advantages and positive effects of the modified zinc anode preparation method, the modified zinc anode, and the aqueous zinc-ion battery described in this invention are as follows: 1. This invention involves immersing the zinc anode in a tetrahydroxymethyl phosphorus chloride treatment solution to form a thin protective layer on the surface of the zinc anode and activate the crystal face to obtain a passivation-activation structure, which effectively inhibits the formation of zinc dendrites, reduces side reactions between the zinc anode and the electrolyte, and effectively improves the cycle life of aqueous zinc-ion batteries.
[0019] 2. The method described in this invention completes the reaction between the zinc anode and the tetrahydroxymethyl phosphorus chloride treatment solution at room temperature, which has low equipment requirements, is simple to operate, effectively reduces costs, and reduces the difficulty of preparing modified zinc anodes.
[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0021] Figure 1 The images shown are scanning electron microscope (SEM) images of the untreated zinc anode in Comparative Example 2 of the present invention, and the modified zinc anodes prepared in Examples 1, 2 and 3; (a), (b) and (c) are SEM images of Comparative Example 2, (d), (e) and (f) are SEM images of Example 1, (g), (h) and (i) are SEM images of Example 2, and (j), (k) and (l) are SEM images of Example 3. Figure 2 The images are scanning electron microscope (SEM) images of the zinc electrode surface treated with tetramethylphosphoric acid solution in Example 4; (a) is an SEM image at 200 μm, (b) is an SEM image at 20 μm, (c) is an SEM image at 5 μm, and (d) is an SEM image at 2 μm. Figure 3 The cycling performance of the symmetrical batteries assembled in Examples 1, 2, 1, and 2 of the present invention is shown in (a) for Example 1, (b) for Example 2, (c) for Comparative Example 1, and (d) for Comparative Example 2. Figure 4 The full cell assembled with the zinc anode and ammonium vanadate cathode as described in Example 1 of this invention, at 1A g -1 Cyclic performance at current density. Detailed Implementation
[0022] In this application, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. In case of any inconsistency, the meaning set forth in this specification or derived from the content described herein shall prevail. Furthermore, the terminology used herein is for the purpose of describing embodiments of this application only and is not intended to limit the scope of this application.
[0023] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0024] A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) tetrahydroxymethylphosphoric acid (THPC) solution to a certain concentration and stir until homogeneous to form a treatment solution. The volume concentration of THPC in the prepared treatment solution is 1%-7%. If the concentration of THPC is too low, it will not be able to effectively etch the zinc electrode; if the concentration is too high, it will lead to excessive exposure of the active crystal face, thereby aggravating side reactions.
[0025] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0026] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0027] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove oil stains from the surface of the zinc anode. After cleaning, it is dried.
[0028] S3. Immerse the treated zinc anode in a tetrahydroxymethylphosphoric acid solution at room temperature to allow the reaction to occur. The reaction time is 0.5 h to 10 h.
[0029] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0030] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0031] A modified zinc anode, comprising: Zinc anode body, An active zinc electrode structure is formed by etching a zinc substrate on the surface of the zinc anode body using THPC and simultaneously forming a passivation layer protected by the product coating. This passivation-activation structure is formed by the above preparation method.
[0032] The zinc anode body is made of pure zinc foil or pure zinc plate.
[0033] Tetramethylphosphorus chloride preferentially adsorbs onto the zinc electrode surface, first reacting with the surface passivation layer to remove the surface oxide film. Subsequently, it reacts with Zn... 2+ Coordination occurs, etching the zinc substrate to expose the active crystal facets. Simultaneously, the phosphorus-containing compounds generated by the reaction cover the zinc substrate to form a uniform protective layer, ultimately obtaining a zinc electrode structure with a passivation-activation structure.
[0034] If the concentration of THPC is too low, it will not provide enough THPC molecules to react fully with the zinc surface, resulting in the inability to remove the oxide layer on the zinc anode surface. If the concentration of THPC is too high, the excess THPC molecules will promote the corrosion reaction, and the exposure of a large number of active crystal faces will exacerbate side reactions such as hydrogen evolution and passivation. Therefore, the volume concentration of THPC in the treatment solution should be 1%-7%.
[0035] If the immersion time of the zinc anode is too short, the reaction between tetrahydroxymethylphosphoric chloride (THPC) and the zinc anode will be insufficient, making it difficult to form a stable passivation-activation structure and thus failing to exert a modifying effect. If the reaction time is too long, the continuous reaction will lead to the destruction of the passivation layer and excessive exposure of the active crystal facets. Therefore, the immersion time of the zinc anode in the treatment solution should be 0.5h-10h.
[0036] The passivation-activation structure formed on the zinc anode surface can suppress uneven deposition of zinc dendrites. Zinc dendrites are a key issue leading to cycle failure in aqueous zinc-ion batteries (they can puncture the separator and cause short circuits). The active zinc substrate significantly increases the specific surface area of the electrode, effectively reducing the local current density, thereby guiding Zn... 2+ To achieve uniform deposition and avoid Zn 2+ Dendrites form due to localized excessive aggregation on the negative electrode surface; simultaneously, the anisotropic crystal planes generated by etching can buffer Zn. 2+ Stress during the deposition / dissolution process maintains the long-term integrity of the electrode structure and effectively improves the cycle life of the battery.
[0037] An inert protective layer on the zinc anode surface can reduce side reactions between the zinc anode and the electrolyte. Water in aqueous electrolytes can react with the zinc anode in ways such as corrosion and hydrogen evolution (generating corrosive byproducts and consuming zinc active materials), leading to decreased coulombic efficiency and shortened cycle life. The anode protective layer effectively isolates the zinc anode surface from direct contact with the electrolyte, significantly reducing hydrogen evolution and the formation of corrosive byproducts; simultaneously, the protective layer does not impede the growth of Zn. 2+ Normal transport (avoiding increased polarization) ensures the protection of Zn while suppressing side reactions (reducing hydrogen evolution and corrosion byproduct formation). 2+ The efficient migration of these components improves the cycle stability and coulombic efficiency of the battery.
[0038] An aqueous zinc-ion symmetric battery includes a zinc electrode, a separator, an electrolyte, and a zinc electrode, wherein the zinc electrode is the modified zinc negative electrode described above.
[0039] The electrolyte for the symmetrical cell is a 2 mol / L ZnSO4 solution, and the membrane is a glass fiber membrane or commercial filter paper.
[0040] An aqueous zinc-ion full battery includes a positive electrode, a separator, an electrolyte, and a zinc negative electrode. The zinc negative electrode is the modified zinc negative electrode described above, the positive electrode is an ammonium vanadate positive electrode, the electrolyte is a 2 mol / L ZnSO4 solution, and the separator is a glass fiber separator or commercial filter paper.
[0041] Example 1 A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) solution of tetramethylolphosphine chloride to a certain concentration, stir well, and form a treatment solution. The volume concentration of tetramethylolphosphine chloride in the prepared treatment solution is 1.25%.
[0042] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0043] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0044] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove oil stains from the surface of the zinc anode. After cleaning, it is dried.
[0045] S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur. The reaction time is 3 hours.
[0046] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0047] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0048] Example 2 A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) solution of tetramethylolphosphine chloride to a certain concentration, stir well, and form a treatment solution. The volume concentration of tetramethylolphosphine chloride in the prepared treatment solution is 1.25%.
[0049] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0050] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0051] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove oil stains from the surface of the zinc anode. After cleaning, it is dried.
[0052] S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur. The reaction time is 6 hours.
[0053] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0054] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0055] Example 3 A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) solution of tetramethylolphosphine chloride to a certain concentration, stir well, and form a treatment solution. The volume concentration of tetramethylolphosphine chloride in the prepared treatment solution is 1.25%.
[0056] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0057] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0058] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove oil stains from the surface of the zinc anode. After cleaning, it is dried.
[0059] S3. The treated zinc anode was immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur. The reaction time was 9 hours.
[0060] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0061] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0062] Example 4 A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) solution of tetramethylolphosphine chloride to a certain concentration, stir well, and form a treatment solution. The volume concentration of tetramethylolphosphine chloride in the prepared treatment solution is 6.25%.
[0063] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0064] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0065] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove oil stains from the surface of the zinc anode. After cleaning, it is dried.
[0066] S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur. The reaction time is 9 hours.
[0067] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0068] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0069] Figure 2 The microstructure of zinc foil etched for 9 hours with 6.25% THPC solution is shown. Figure 2 It can be seen that after treatment with 6.25% THPC solution for 9 hours, obvious crystal planes and grain boundaries can be observed on the surface of zinc foil, but no obvious passivation layer can be observed.
[0070] Comparative Example 1 A method for preparing a modified zinc anode includes the following steps: S1. Dilute an 80% (w / w) solution of tetramethylolphosphine chloride to a certain concentration, stir well, and form a treatment solution. The volume concentration of tetramethylolphosphine chloride in the prepared treatment solution is 1.25%.
[0071] S2. Cut the zinc negative electrode to the required size and perform surface treatment on the zinc negative electrode.
[0072] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0073] The surface treatment of the zinc anode is as follows: the zinc anode is ultrasonically cleaned with deionized water and ethanol in sequence for 30 minutes at a power of 25W to remove the oxide layer and oil on the surface of the zinc anode. After cleaning, it is dried.
[0074] S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur. The reaction time is 15 hours.
[0075] S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
[0076] The drying temperature of the vacuum drying oven is 60℃, and the drying time is 4 hours.
[0077] Comparative Example 2 In this comparative example, the zinc anode was not subjected to immersion treatment with tetrahydroxymethylphosphoric acid. The zinc anode underwent the following treatment.
[0078] The zinc negative electrode is cut to the required size and then surface-treated.
[0079] The zinc anode is 100 μm thick and is made of pure zinc foil or pure zinc plate.
[0080] The surface treatment of the zinc anode involved sequentially ultrasonically cleaning it with deionized water and ethanol for 30 minutes at a power of 25W. After cleaning, the anode was placed in a vacuum drying oven at 60℃ for 4 hours.
[0081] The microstructure of the modified zinc anodes prepared in Examples 1, 2, and 1 was observed, and the scanning electron microscope images are shown below. Figure 1 As shown. From Figure 1 It can be seen that after treatment with the same concentration of THPC solution, the oxide layer on the surface of the zinc anode is gradually etched, and as the treatment time increases, the crystal planes and grain boundaries of metallic zinc are gradually exposed.
[0082] Comparative Example 2: Microstructure of the zinc anode surface without immersion treatment with tetramethylphosphoric acid (TMP) is as follows. Figure 1 As shown, from Figure 1 It can be seen that the zinc electrode surface has a texture produced by processing and manufacturing, and due to the presence of inert compounds (ZnO, Zn(OH)2, etc.), the grain boundaries and crystal planes of zinc cannot be observed on the bare zinc electrode surface.
[0083] The modified zinc anodes prepared in Examples 1-2 and Comparative Examples 1 and 2 were assembled into Zn|Zn symmetrical cells. The electrodes of the symmetrical cells were the modified zinc anodes described above, the electrolyte was a 2 mol / L ZnSO4 solution, and the separator was a glass fiber membrane or commercial filter paper. The assembled symmetrical cells were tested at 1 mA / cm². 2 Current density and 1mAh / cm 2 Constant current charge-discharge test was performed on the surface capacity.
[0084] The cycle performance of the symmetrical batteries assembled in Examples 1, 2, 1 (Comparative Example), and 2 (Comparative Example 2) is as follows: Figure 3 As shown. From Figure 3 As can be seen, although the cycle stability of the zinc anode in the symmetrical cell first increases and then decreases with the extension of treatment time, the cycle life of the zinc anode treated with THPC is much higher than that of the untreated zinc electrode, especially at 1 mA / cm². 2 Current density and 1mAh / cm 2Under the condition of areal capacity, the cycle life of zinc anode treated with 1.25% THPC solution for 3h and 6h is 420h and 1100h respectively, which is much higher than that of untreated zinc anode (less than 100h).
[0085] The cycle performance of the full cell based on the zinc anode and ammonium vanadate cathode prepared in Example 1 after 1000 cycles at a current density of 1 A / g is as follows: Figure 4 As shown in the figure, after 1000 cycles, a discharge specific capacity of 167 mAh / g can still be obtained.
[0086] Therefore, the modified zinc anode preparation method, modified zinc anode, and aqueous zinc-ion battery described in this invention can solve the problems of poor cycle stability, difficult preparation, and high cost of modified zinc anode.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a modified zinc anode, characterized in that, Includes the following steps: S1. Dilute the 80% tetrahydroxymethyl phosphorus chloride solution to a certain concentration, stir evenly, and form a treatment solution; S2. After cutting the zinc negative electrode, perform surface treatment on the zinc negative electrode; S3. The treated zinc anode is immersed in a tetrahydroxymethylphosphoric acid treatment solution at room temperature to allow the reaction to occur; S4. After the reaction is complete, rinse the surface of the zinc anode with deionized water and anhydrous ethanol to remove the residual solution, and then dry it in a vacuum drying oven to obtain the modified zinc anode.
2. The method for preparing a modified zinc anode according to claim 1, characterized in that: In S1, the volume concentration of tetrahydroxymethylphosphoric acid in the prepared treatment solution is 1%-7%.
3. The method for preparing a modified zinc anode according to claim 1, characterized in that: In S2, the thickness of the zinc negative electrode is 100 μm, and the zinc negative electrode is pure zinc foil or pure zinc plate.
4. The method for preparing a modified zinc anode according to claim 1, characterized in that: In step S2, the surface treatment of the zinc anode specifically involves ultrasonically cleaning the zinc anode with deionized water and ethanol in sequence for 30 minutes at a power of 25W.
5. The method for preparing a modified zinc anode according to claim 1, characterized in that: In S3, the reaction time is 0.5h-10h.
6. The method for preparing a modified zinc anode according to claim 1, characterized in that: In step S4, the drying temperature of the vacuum drying oven is 60°C, and the drying time is 4 hours.
7. A modified zinc anode, characterized in that, include: Zinc anode body, A passivation-activation structure is formed in situ on the surface of the zinc anode body, and the passivation-activation structure is formed by the preparation method described in any one of claims 1-6.
8. A modified zinc anode according to claim 7, characterized in that: The thickness of the zinc anode body is 100μm, and the zinc anode body is pure zinc foil or pure zinc plate.
9. An aqueous zinc-ion battery, a complete battery, comprising a positive electrode, a separator, an electrolyte, and a zinc negative electrode, characterized in that: The zinc anode is the modified zinc anode as described in claim 8, the cathode is ammonium vanadate cathode, the electrolyte is a 2 mol / L ZnSO4 solution, and the diaphragm is a glass fiber diaphragm or commercial filter paper.
10. An aqueous zinc-ion battery, which is a symmetrical battery, characterized in that: It includes a zinc electrode, a diaphragm, an electrolyte, and a zinc electrode, wherein the zinc electrode is the modified zinc negative electrode as described in claim 8, the electrolyte is a 2 mol / L ZnSO4 solution, and the diaphragm is a glass fiber diaphragm or commercial filter paper.
Citation Information
Patent Citations
Surface organic phosphoric acid etched composite zinc-philic passive film modified zinc metal negative electrode as well as preparation method and application thereof
CN113964289A
Method for in-situ generation of protective film on surface of metal anode of zinc ion battery and application thereof
CN115528319A
Additive of aqueous zinc ion battery, electrolyte and aqueous zinc ion battery
CN119009159A
Phosphorus-containing zinc ion battery negative electrode modifier, modification method and application thereof
CN119069706A
Cited By
Modified aqueous zinc battery negative electrode and preparation method thereof
CN121983507A